UTILIZATION OF MEMBRANE MICROFILTRATION IN PREPARATION OF HYDROLYZED VEGETABLE PROTEIN FROM FERMENTED RED BEAN (Phaseolus vulgaris L.) EXTRACT AS FORTIFICATION AGENT - Sri Moerniati; Agustine Susilowati; Aspiyanto Aspiyanto (Indonesian Journal of Chemistry, 2009)
Preparation of Hydrolyzed Vegetable Protein (HVP) as savory flavor from fermented red bean broth through stirred membrane cell using micro filtration membrane with pore size of 0.45 µm was performed to get fortified agent utilized in preparation of beans sauce. The objective of this work was to study an effect of pressure and kind of red bean broth extract on content of total protein, soluble protein and dry solid in the retentate and permeate as hydrolyzed vegetable protein used for fortified agent of red bean sauces. Preparation process of hydrolyzed vegetable protein was done using fixed rotary speed of 400 rpm, pressure of 20, 25 and 30 psi at room temperature. To investigate the effect of pressure on this separation, the feed were red bean broth extract fermented for 6, 8, 10 and 12 weeks, respectively. Fermentation process were conducted using salt fermentation with inoculum of Rhizopus-C1, salt and red bean ratios of 30:10:60%. The analysis of flux and contents of total protein, dissolved protein and dry solid in the retentate and permeate was carried out, and the result of experiment showed that interaction of Red bean broth extract with 6, 8, 10 and 12 weeks of fermentation and operation condition of microfiltration membrane separation tends to affect on flux and content of total protein, dissolved protein and dry solid in retentate and permeate. Red bean broth extract for 6 weeks fermentation resulted higher protein content in permeate as hydrolyzed vegetable protein than in retentate. Permeate at pressure of 25 psi gives flux value of 0.0217 mL/cm2.minute and contents of total protein of 1.31 %, dissolved protein of 6.9 mg/g, and dry solid of 2.6%, while retentate as hydrolyzed vegetable protein or fortified agent indicate contents of total protein of 1.52%, dissolved protein of 4.15 mg/g, and dry solid of 3.64%. It was found that micro filtration process was able to increase dissolved protein content of about 3 times.